Dari Weberian hingga Indonesiasentris: kajian historis-sosiologis B.J.O Schrieke serta kontribusinya bagi historiografi Indonesia - Mochammad Ronaldy Aji Saputra (Historiography: Journal of Indonesian History and Education, 2022)
This study aims to review the Weberian concept developed by B.J.O Schrieke and its contribution to the development of Indonesian historiography. This study uses the library method with an autobiographical approach. The results of the study show that Schrieke has shown historiography with a socio-cultural perspective and has succeeded in revealing many aspects of society and the life of the Indonesian people. This can be seen through Schrieke's works, namely het boek van Bonang (1916) and Indonesian Sociological Studies (1955). Schrieke was inspired by Max Weber's way of explaining history from various socio-historical perspectives. Schrieke's sociological historical thought influenced the basic framework of subsequent Indonesian history writing.Penelitian ini bertujuan untuk mengulas konsep Weberian yang dikembangkan oleh B.J.O Schrieke serta kontribusinya bagi perkembangan historiografi Indonesia. Penelitian ini menggunakan metode kepustakaan dengan pendekatan otobiografi. Hasil penelitian menunjukan bahwa Schrieke telah menunjukkan bentuk historiografi dengan perspektif sosial-budaya dan berhasil mengungkap banyak aspek kemasyarakatan dan kehidupan bangsa Indonesia. Hal ini dapat diketahui melalui karya-karya Schrieke yaitu het boek van Bonang (1916)dan Indonesian Sociological Studies (1955). Schrieke terinspirasi cara berpikir Max Weber dalam menjelaskan sejarah dengan berbagai perspektif sosio-historis. Pemikiran historis sosiologis Schrieke berpengaruh terhadap kerangka dasar penulisan sejarah Indonesia selanjutnya.